2008
DOI: 10.1161/hypertensionaha.107.100941
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Mineralocorticoid Receptor Blockade Improves Myocardial Infarct Healing by Modulation of the Inflammatory Response

Abstract: Abstract-Mineralocorticoid receptor (MR) blockade reduces morbidity and mortality after acute myocardial infarction; however, the underlying mechanisms are still under investigation. This study examined whether MR antagonism promotes healing of the infarcted myocardium. Starting immediately after coronary ligation, male Wistar rats were treated with the selective MR antagonist eplerenone (100 mg/kg per day by gavage) or placebo for 2 to 7 days. At 7 days, eplerenone therapy versus placebo significantly reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 114 publications
(87 citation statements)
references
References 47 publications
2
83
1
1
Order By: Relevance
“…Mill et al (17) showed that aldosterone also contributes to increased collagen deposition in non-infarcted viable tissue. Another effect of aldosterone observed in infarcted rats showed that immediate treatment with eplerenone, a selective aldosterone antagonist, improved left ventricular function and reduced deleterious effects of cardiac remodeling by modulation of inflammatory response in acute phase of the healing process (36). This was mediated by acceleration of macrophage infiltration and necrotic re-absorption.…”
Section: The Cardiac Renin-angiotensin-aldosterone Systemmentioning
confidence: 98%
“…Mill et al (17) showed that aldosterone also contributes to increased collagen deposition in non-infarcted viable tissue. Another effect of aldosterone observed in infarcted rats showed that immediate treatment with eplerenone, a selective aldosterone antagonist, improved left ventricular function and reduced deleterious effects of cardiac remodeling by modulation of inflammatory response in acute phase of the healing process (36). This was mediated by acceleration of macrophage infiltration and necrotic re-absorption.…”
Section: The Cardiac Renin-angiotensin-aldosterone Systemmentioning
confidence: 98%
“…29 Increased oxidative stress, inflammation, and fibrosis are evident in several animal models of cardiac and renal diseases (eg, rats post-MI, dogs with HF, and uninephrectomized diabetic rats). 18,[38][39][40] Furthermore, MR activation stimulates apoptosis and causes vasoconstriction and reduced blood flow in the animal heart and kidneys. 8,18,41,42 Reduced endothelium-dependent vasodilatation is thought to be caused by an aldosterone-mediated decrease in the bioavailability of nitric oxide.…”
Section: February 2015mentioning
confidence: 99%
“…[1][2][3][4] However, it remains unclear whether the cardioprotective effects of MR antagonists can be attributed to inhibition of the cardiomyocyte MR. While attenuation of left ventricular (LV) dilation and excessive extracellular matrix turnover [5][6][7][8][9] and prevention of electric remodeling appear to be essential mechanisms of MR antagonism, 10,11 extracardiac effects such as renal sodium excretion and potassium sparing, restoration of autonomic balance, and improvement in vascular endothelial dysfunction may be of particular importance. 9,[12][13][14] …”
mentioning
confidence: 99%